Design and test of active porosity mechanism for UAV maneuving - Soh, Angela Kah Sin (2014)
With the rising demand for unmanned vehicles, including small unmanned aerial vehicles (UAVs), in various applications ranging from military to commercial uses, it is imperative to expand their capabilities to meet modern needs. Enhancing maneuverability is one area of capability, which can be further strengthened. Active porosity mechanism, a flow control technique, presents a solution to provide additional maneuverability through the creation of differential aerodynamic forces over an airplane body. The possibility of delaying stall for expansion of flight envelope provides greater maneuverability as well. In this project, an active porosity mechanism with the capability of providing time periodic actuation to create unsteady flow excitation has been developed. Wind tunnel tests were conducted over a range of angles of attack and actuation frequencies, and the aerodynamic performance was examined. The results showed the improved performance achieved by the porosity mechanism. However, within the range of frequencies actuated by the valve, there was no significant change in aerodynamic performance. Discussion of the results led to recommendations to improve on the wing model prototype. Ideas to further the study were also provided.